2010
DOI: 10.1108/13552541011034898
|View full text |Cite
|
Sign up to set email alerts
|

Advanced process planning for subtractive rapid prototyping

Abstract: This paper presents process planning methods for Subtractive Rapid Prototyping, which deals with multiple setup operations and the related issues of stock material management. Subtractive Rapid Prototyping (SRP) borrows from additive rapid prototyping technologies by using 2½D layer based toolpath processing; however, it is limited by tool accessibility. To counter the accessibility problem, SRP systems (such as desktop milling machines) employ a rotary fourth axis to provide more complete surface coverage. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The quality of milled models has historically been poor because soft and brittle PUT foam was used, and there was limited development of the milling machine 6,29. However, the recent use of high strength PUT blocks and multiple-axis milling machines enables production of a variety of complex geometries from a vast array of materials 30. Further studies are required incorporating patients under clinical conditions as subjects, that may involve missing or malpositioned teeth and fixed dental prostheses, because this study was limited to the use of a standard master model and duplicated sample models, in a laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of milled models has historically been poor because soft and brittle PUT foam was used, and there was limited development of the milling machine 6,29. However, the recent use of high strength PUT blocks and multiple-axis milling machines enables production of a variety of complex geometries from a vast array of materials 30. Further studies are required incorporating patients under clinical conditions as subjects, that may involve missing or malpositioned teeth and fixed dental prostheses, because this study was limited to the use of a standard master model and duplicated sample models, in a laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the niche area of Subtractive Rapid Prototyping is particularly appropriate, where automatically planning for custom natural bone implants is the overarching challenge. Although previous research has applied rapid machining (CNC-RP) to fully automated process planning for industrial components [3843], the challenge of rapid machining of natural bone begins with choosing a proper “harvesting” location from which to extract the bony geometry of the implant from within the donor bone. In other words, one is faced with the challenge of finding a suitable location from which to machine an arbitrary free-form shaped object from within another arbitrary free-form shaped stock material object, where each has a unique material density distribution.…”
Section: The Matryoshka Shell Modelmentioning
confidence: 99%
“…While this method normally operates in image space, it analyzes vertically-oriented slices, such that the same set of slices can be used to analyze any orientation in a four-axis mill. Previous work by the authors has demonstrated the advantages of modeling discrete-orientation multi-axis milling with slices oriented along a common axis of rotation [16]. We continue this practice by analyzing the transient stock state with a novel hybrid method of machinability analysis.…”
Section: Figure 3 Consider Machining a Femur (B) From Round Bar Stocmentioning
confidence: 99%